STUDENTS’ COLLABORATION FOR ACTIVE LEARNING IN VOCATIONAL EDUCATION AND TRAINING IN INDONESIA THROUGH APPRENTICESHIP - Adi Maulana; Jianjun Gu; Qiuyue Yang (OISAA, 2020)
ABSTRACTThis research aims to explain collaboration for active learning of vocational students through apprenticeships in West Java province, This program is to support Indonesia government program to revitalize vocational education in accordance with Presidential Instruction to improve human development index in Indonesia. This research involves 520 students taking apprenticeship in grade 11 from several vocational school in West Java Province. The participating schools were purposely selected by the first professional certification institution who conducted the field research through questionnaire answered. The results with from statistics descriptive of five indicators, which are student collaboration for active learning in apprenticeship showed that working together, obeying general rule, good speaking, respect and professionalism with positive ethics is more 35% (n = 520). It is very clear that collaboration is carried out by students from different schools. On the other hand, the role of the instructor is very helpful in apprenticeship. Possible explanation is that the finding of student collaboration using questionnaire answered for active learning in context vocational education and training has limitations to this research. It is indicated that further research be useful to be conducted by other researchers.